Relocation Model of Waqf Land and Buildings Impacted by Sidoarjo Mud Blowout - Rokhim, Abdul; Suratman, Suratman (Al-Risalah, 2021)
This research aims to analyse the validity relocation of land and buildings that cannot be used according to the aim of waqf stipulated in the Islamic Sharia and the Law on Waqf, as well as the relocation model of land and buildings that are impacted by the Sidoarjo mud blowout. This is juridical-normative research that uses statutory and conceptual approaches. The results show that there are dissents among Islamic law experts on the permissibility of waqf object relocation. Then, the Law on Waqf prohibits waqf diversion, except for public interests. Then, the Presidential Decree No. 14 of 2007 and its changes do not regulate waqf object replacement. Even so, in 2020 the government has relocated 8 out of 50 waqf objects outside of the Map of Impacted Area through build swap (ruilslag), whereas none of the waqf objects within the Map of Impacted Area that is the obligation of PT Lapindo Brantas company have been substituted. According to Article 15 clause (1) and (3) of the Presidential Decree No. 14 of 2007, the waqf land or buildings should be relocated using the sales transaction scheme. Its proceeds will then be used to buy substitute waqf objects elsewhere.